THE STUDY OF SERUM LIPID PROFILE IN PREGNANCY INDUCED HYPERTENSION IN JMC, JHALAWAR. - Jat, Dr. Nanu Ram; Gupta, Dr. Ritu; Gupta, Dr. Ayushi (Journal of Biomedical and Pharmaceutical Research, 2019)
Only one group was investigated for serum lipid profile in third trimester of pregnancy in which included all PIH patients admitted in labor room in Department of Obstetrics in Jhalawar Medical College and was substantially compared with the normal values of Lipids in women. In this study we investigate the role of lipid profile in PIH. LDL value increase, HDL value decrease, TG value increase and VLDL value increase in PIH patients and also TG : HDL ration increased significantly in PIH patients. Dyslipidemia mediated activation of endothelial cells to placentally derived endothelial disturbing factors like lipid peroxides and trophoblastic components as possible contributors for pathogenesis of PIH. Thus assessment of blood lipids may be helpful in preventions of complications in PIH.Key Words: Bloodlipids, PIH, Dyslipidemia, Triglycerides, Low Density Lipoprotiens, High Density Lipoprotiens.